تأثير وسط الزراعة في إنتاج فطر المحار Oyster Mushroom (Pleurotus ostreatus) السلالة HK-35 - حميدان, مروان; مخول, سهيل; أحمد, لونا (Latakia University Journal -Biological Sciences Series, 2019)
جرت دراسة تأثير سبعة أوساط زراعية ( قش القمح، التبن، قوالح الذرة، أحطاب القطن، قش القمح 50% + قوالح الذرة 50% ، قش القمح 50 % + أحطاب القطن 50% ، نشارة الخشب 50 % + قش القمح 50% ) في إنتاج فطر المحار Pleurotus ostreatus السلالة HK-35 ( مصدرها إيطاليا )، واعتبر وسط التبن كشاهد. أظهرت النتائج تفوق وسط قش القمح معنوياً على جميع الأوساط الأخرى ماعدا وسط التبن فكانت الفروق غير معنوية ، وبلغ إنتاجه 2.17 كغ / كيس سعة 7 كغ ( وسط رطب ) بكفاءة تحول حيوي 86.80%؛ كما لوحظ تفوق وسط التبن معنوياً على الأوساط : أحطاب القطن ، قوالح الذرة ، قش القمح 50% + قوالح الذرة 50% ، نشارة الخشب 50% + قش القمح 50% حيث بلغ إنتاجه 2.08 كغ / كيس بكفاءة تحول حيوي 83.20%، أما الفروق بين وسط التبن ووسط قش القمح 50% + أحطاب القطن 50% فكانت غير معنوية. This work deals with the effect of seven substrates (wheat straw, hay, corncobs, cotton wastes, corncobs 50% + wheat straw 50%, cotton wastes 50 % + wheat straw 50% and sawdust 50 % + wheat straw 50% ) on the production of oyster mushroom Pleurotus ostreatus strain HK-35. The results showed the significant superiority of the wheat straw substrate over the others except for the hay substrate (whose differences were not significant), where the yield was 2.17 kg / bag content 7 kg ( weight of wet substrate ) with 86.80 % biological efficiency. The hay substrate had significant superiority over the substrates: cotton waste, corncobs, corncobs 50% + wheat straw 50% and sawdust 50% + wheat straw 50%, where its yield was 2.08 kg/bag with 83.20 % biological efficiency, while the productivity differences between this substrate and the cotton waste 50 % + wheat straw 50% substrate was insignificant.